The Role of Landscape in the Formation of Ecotourism Objects on the Territory of Uzbekistan - M., G`aybullaeva (Researchparks Publishing, 2023)
In the article, the authors provide information (landscape solutions for historical monuments, etc.). An attempt is made to analyze the tourist and landscape solution of historical monuments of Samarkand.